Decision-Making Analysis for Forklift Procurement at PT XYZ using the Analytical Hierarchy Process Approach and Engineering Economics Analysis - Ferry, Roy; Fauzi, Muchammad (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
One of the commonly used equipment for transporting goods from one location to another is the forklift. Observations indicate that the availability rate of rented forklift units at PT XYZ is better than that of company-owned units. The purpose of this study is to analyse the decision-making process for forklift procurement at PT XYZ. The selection of the best forklift rental supplier will utilize the AHP method, while the economic analysis for forklift procurement will utilize decision analysis tools such as NPV and BCR. The study results show that the supplier SML (Heli) has the highest priority weight of 0.3419. The economic analysis using the NPV and BCR methods reveals that rental procurement is more favourable than purchase the unit. Thus, it can be concluded that renting forklift units from supplier SML (Heli) is the optimal decision for the company. Peralatan yang sering digunakan untuk mengalirkan barang dari satu tempat ke tempat yang lain salah satunya adalah forklift. Dalam pengamatan didapatkan bahwa tingkat ketersediaan unit forklift sewa di PT XYZ lebih baik dibandingkan dengan tingkat ketersediaan unit milik sendiri. Tujuan dari penelitian ini adalah untuk menganalisis pengambilan keputusan pengadaan forklift di PT XYZ. Pemilihan supplier sewa forklift terbaik akan menggunakan metode AHP. Sedangkan analisis ekonomi teknik pengadaan forklift menggunakan tools analisis keputusan yaitu NPV dan BCR. Dari penelitian dihasilkan keputusan bahwa supplier SML (Heli) memiliki bobot prioritas tertinggi sebesar 0,3419. Analisis ekonomi teknik dengan metode NPV dan BCR menunjukkan pengadaan sewa lebih baik dibandingkan pengadaan beli. Sehingga dapat disimpulkan keputusan sewa unit forklift ke supplier SML (Heli) adalah keputusan terbaik bagi perusahaan.